ASSISTANCE IN DRAFTING AN EMPLOYMENT CONTRACT LIMITED TIME AT PT. SARANA INSPIRASI MAJU BERSAUDARA - Shenti Agustini; Velany Kosasih (ConCEPt - Conference on Community Engagement Project, 2022)
Employment Contract Limited Time (PKWT) is a work agreement between workers and the company in establishing a working relationship for a certain period of time or for certain jobs. The latest regulations governing PKWT are Government Regulation Number 35 of 2021 concerning Employment Contract Limited Time, Outsourcing, Working Time, and Rest Time, and Termination of Employment. In a company, PKWT is one of the important documents because it can be valid evidence for both parties, namely the employee and the company. Therefore, the authors are encouraged to contribute in the form of PKWT design which is expected to help the company PT. Sarana Inspirasi Maju Bersaudara in creating good working relationships with workers in carrying out their business activities. The main problem is that adjustments must be made to the latest law, but PT. Sarana Inspirasi Maju Bersaudara has not carried out the adjustment due to the lack of manpower in the legal field. The implementation method used in this report uses empirical juridical. The empirical juridical method is a type of legal research that is examined directly in the field in the form of examining company documents or data obtained in the field which is then adjusted to the applicable law.